Changing the innate consensus about mesh fixation in trans-abdominal preperitoneal laparoscopic inguinal hernioplasty in adults: Short and long term outcome. Randomized controlled clinical trial. (November 2020) - Habeeb, Tamer.A.A.M.; Mokhtar, Mohammed Mahmoud; Sieda, Bassem; Osman, Gamal; Ibrahim, Amr; Metwalli, Abd-Elrahman M.; Riad, Mohamed; Khalil, Osama M.H.; Mansour, Mohamed Ibrahim; Elshahidy, Tamer Mohamed; Abdelhamid, Mohamed I.; Mohamed, Moustafa B.
Abstract: Introduction: Inguinal hernioplasty is the standard treatment for inguinal hernia in adults. Mesh fixation was used to keep mesh in place for which various mesh fixation techniques have been used in laparoscopic inguinal hernia repair in adults, but their effectiveness has remained inconclusive. Aim of the work: to evaluate non fixation method of mesh laparoscopic inguinal hernioplasty as safe and effective as regard short and long term outcomes. Patients and methods: Over the period from July 2013 to July 2018, 798 patients with oblique inguinal hernias undergoing Trans abdominal preperitoneal technique (TAPP) were randomized into 3 groups: Group A; mesh non fixation 266 patients. Group B; tacker mesh fixation 266 patients Group C: Cyanoacrylic tissue glues (Histoacryl) mesh fixation 266 patients. Clinical effects were assessed by the following variables: intraoperative data, postoperative outcome as regard recurrence rate, postoperative pain [on visual analogue score (VAS)], analgesic consumption, operation time, hospital stay, and patient costs. Follow up was 18 months. Results: There was no statistical difference between groups (A) and Group (C) regarding operative time, postoperative complications, and length of hospital stay and risk of chronic groin pain, postoperative pain score. In Group (B): the postoperative pain and complications were higher. There were 5 cases of hernia recurrence in all groups, but no significant differences among the three groups. Conclusion: Tacker Mesh fixation increased the risk of chronic groin pain. Pain score was higher with tacker mesh fixation. Laparoscopic TAPP inguinal hernia repair without tacker mesh fixation was safe and feasible with no significant increase in recurrence rates. Furthermore, mesh fixation with tacker procedure increased the risk of postoperative complications and patient costs. All ethical approval was given by our Faculty of Medicine medical ethical committee. Highlights: Inguinal hernia is commonly met in clinical practice. Laparoscopic hernioplasty is better than open hernioplasty. Different methods of mesh fixation emerged in last decades. Non fixation and histoacryl mesh fixation is better than tacker fixation.